Dermoscopy in the Diagnosis of Cutaneous Leishmaniasis - Gamze Serarslan; Özlem Ekiz; Cahit Özer; Gökhan Sarıkaya (Mattioli1885, 2019)
Background: Cutaneous leishmaniasis (CL) is a protozoan infectious disease. Dermoscopy is a noninvasive diagnostic tool that has been applied to several skin diseases, including infestations. Objectives: To determine the dermoscopic patterns of CL lesions and to investigate whether a relationship exists between dermoscopic characteristics and the disease duration, localization, and type of CL lesions. Methods: Seventy-nine patients (48 male, 31 female) from Hatay, Turkey, were enrolled in the study and a dermoscopic evaluation was performed on 139 lesions. Images of CL lesions were taken via polarized light contact dermoscopy. Chi-square and Fisher exact tests were used for statistical analyses and P values <0.05 were considered significant. Results: Generalized erythema was seen in all CL lesions. Vascular structures (94.2%), yellow tears (75.5%), and a white starburst-like pattern (58.3%) were the other most common dermoscopic features. Hyperkeratosis (P = 0.001) and white starburst-like pattern (P < 0.001) were more prevalent in the extremities than elsewhere. Among vascular structures, linear irregular (45.8%), hairpin (43.5%), and comma-shaped (25.9%) patterns were the most common dermoscopic findings. Linear irregular (P = 0.023) and arborizing vessels (P = 0.001) were observed in the head-neck region. Dotted (P = 0.009), hairpin (P < 0.001), and glomerular-like (P = 0.016) morphological findings were more prevalent in the extremities. Statistical significances in disease duration were detected in microarborizing (P = 0.027) and arborizing (P = 0.004) vessels and were most prevalent with a disease duration of >6 months. Hairpin vessels were prevalent in the plaque and nodulo-ulcerative type of lesions. Dotted vessels were most commonly seen in the plaque type (47.4%) of lesions. Conclusions: Generalized erythema, yellow tears, and starburst-like patterns, as well as linear irregular, hairpin, comma-shaped, and arborizing vessels, were the most commonly detected dermoscopic features of CL lesions. We suggest that the presence of these features can be helpful when diagnosing CL lesions by dermoscopy.